Implikasi Pilar Humanisasi Pendidikan Profetik Dalam Pendidikan Karakter - Wahyu Ningsih; Paidatun Nisa; Tri Septiyani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article entitled The Implications of the Humanization Pillar of Prophetic Education in the Concept of Character Education is a qualitative research using a literature approach, specifically a study that analyzes data based on written materials. The literature used consists of published notes, books, magazines, newspapers, manuscripts, journals or articles. The results of this study indicate that the humanization pillar plays an important role in the concept of character education based on prophetic education. Therefore, character education based on prophetic education should be able to integrate the pillars of humanization in character development.